ЭКТОПИЯ ПОДЖЕЛУДОЧНОЙ ЖЕЛЕЗЫ В ПРАКТИКЕ ПЕДИАТРА: КЛИНИЧЕСКИЙ СЛУЧАЙ - Налетов, Андрей Васильевич; Чалая, Любовь Феликсовна; Москалюк, Оксана Николаевна; Бычков, Данил Вячеславович; Разгонов, Валерий Иванович (FORCIPE, 2022)